Opportunities and Obstacles in Individualized Pay-setting From a Manager Perspective - Malmrud, Sofia; Falkenberg, Helena; Lindfors, Petra; Hellgren, Johnny; Sverke, Magnus (Nordic Journal of Working Life Studies, 2023)
This study explored pay-setting managers’ experiences regarding the individualized pay-setting process. Seven semi-structured group-interviews with pay-setting managers (N = 28) from four private companies in Sweden were conducted. A thematic analysis identified three main themes: 1) Prerequisites for pay-setting, which included conditions for pay-setting work and experiences of these conditions; 2) Assessment and feedback, which included experiences of employee performance assessment and feedback provision; 3) Rewards, which covered experiences of different pay incentives and the relationship between performance and pay. The pay-setting process was considered to include many obstacles as well as a few opportunities. Without proper pre-requisites to assess employee performance, the possibilities to adequately reward performance were experienced as limited, which, in turn, hampered possibilities to justify both the assessment and pay raise. Taken together, this study underscores the conflict between intentions relating to how to carry out a pay-setting process and managers’ difficulties to actually accomplish this.